Evaluation of miR-195-5p Expression and Determine Some Immunological Markers in Hospitalized Patients with Severity COVID-19 - Al-Rekaabi, Aseel Razak; Al-Deresawi, Mahdi Saber (Journal of Science in Medicine and Life, 2025)
COVID-19 pandemic due to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a unique global health crisis that ended up causing considerable morbidity and mortality in all age groups worldwide. This analysis tried to explore the regulation expression of endogenous miR-195-5p and its impact in levels of IL-6, IL-8 and TNF-α. This study includes 50 severe COVID-19 patients against a control population of 25 healthy controls. The results indicated that the highest number of patients' group ranged between 40-50 years and this represented by 20((40.00%) followed by the patients' group who was between >50 years old which was 19 (38.00%) and 11(22.00%) in patients with <40 years, on the other hand; ELISA assay showed there were a highly significance in IL-6 (5.582 ±0.29 ng/ml) and TNF-α showed (151.82 ±13.19 ng/ml), when compared to healthy control group (2.664 ±0.21 ng/ml) and (54.63 ±8.87 ng/ml)respectively, while there were a significant increase in IL-8 levels (29.73 ±5.56 ng/ml) compared to healthy control group (22.65 ±1.14 ng/ml). The Expression of the miR-195-5p gene was decreased in high significantly decrease (P≤0.01) in patients (0.374 ±0.18) fold compared to control that recorded (1.00 ±0.00). In conclusion, the decreased expression of miR-195-5p in severity COVID-19 patients can contribute in increment of IL-6, IL-8 and TNF-α levels because the lack its role consequently increase the cytokine storm.